A survey of radiographic prescription in dental implant assessment - Sakakura, C. E.; Morais, JAND; Loffredo, LCM; Scaf, Gulnara [UNESP] (British Inst Radiology, 2003)
Objectives: To survey the current radiographic prescriptions in dental implant assessment amongst dentists in Brazil.Methods: Sixty-nine dentists were interviewed during a dental implant meeting by two calibrated graduate students, using a 19-question questionnaire, considering imaging modality options both for pre-operative implant site assessment and for follow-up, particularly with respect to cost, patient radiation dose, and broad coverage of facial bones and teeth. Epi-Info 6.04 software was used to analyse the database file.Results: Approximately 63.8% of the dentists prescribed only panoramic radiography for dental implant assessment and 28.9% ordered panoramic radiography plus periapical radiography and/or conventional tomography and/or computed tomography (CT). Only 7.2% of the dentists ordered conventional tomography or CT as a single examination, although 10.1% ordered it in combination with other imaging modalities. The main reasons given for prescribing panoramic radiography were broad coverage and cost (86.4%).Conclusions: This study has shown that most of the dentists in this study prescribe panoramic radiographs in dental implant assessment based on broad coverage and cost. They are not following the American Academy of Oral and Maxillofacial Radiology recommendations regarding cross-sectional imaging.
Keywords: survey; dental radiography; dental implants; tomography; X-ray computed